A constituição ética dos apóstolos Paulo e Pedro em textos bíblicos - Silveira, Carlos Cesar (2013)
This dissertation presents an analysis of the ethos of the apostles Paul and Peter manifested in biblical texts. The corpus of the analysis is constituted by the II Epistle of Paul to the Corinthians and by the I Epistle from Peter to the Jews. The goal of the study is to identify and confront, through a qualitative and quantitative analysis, the ethos of the two most important leaders of Christianity, the apostles Paul and Peter. The theoretical framework used in this work includes the establishing of the ethos from the rhetorical studies grounded in the conceptions of Aristotle (1964), Meyer (2007), Charaudeau (2011), Reboul (2004), Amossy (2005), and Tringali (1988). The results of the analysis showed the manifestation of the ethical and pathetic arguments by the apostles Paul and Peter, respectively. Paul, by his high level of education, made constant use of the ethical arguments. Besides this, he looked for persuading his audience through the rhetorical art and the reasoning. Peter, who didn´t have the same intellectual capacity of Paul, looked for persuading his audience through the pathetic arguments, in other words, he availed himself of the emotion and the affection. The analysis also demonstrated that the ethical arguments used by Paul led him to express the ethos of knowledge, credibility, authority, choice, identity, leadership, comforter, joy, solidarity, competence, confidence, eloquence, serious and overcoming. The pathetic arguments used by Peter led him to manifest the ethos of choice, generosity, compassion, kindness, humanity and preacher. We still certify that both apostles expressed in the same way the ethos of virtue and holiness in the corpus analyzed.